(untitled) (Bangladesh Journal of Otorhinolaryngology, 2010)
Objective: To evaluate the improvement of hearing after stapedial surgery, to record the problems during surgery and to assess the complications of the same. Study design: Retrospective review. Setting: Department of Otolaryngology & Head and Neck Surgery, Bangabandhu Shiekh Mujib Medical University. Materials and Methods: This study included thirty two patients of otosclerosis that were surgically treated in the department of otolaryngology and Head-Neck surgery at BSMMU from January, 2003 to June, 2005. The data of each patient included age, sex, educational & socio-economic status, mode of admission, types of dwelling, occupation, presenting symptoms and signs, preoperative investigations like PTA, tympanometric compliance, stapedial reflex, speech discrimination, HRCT temporal bone(in suspected cases of obliterated otosclerosis), operation notes, complications of surgery and state at follow up. Results: Most common age group was 21-30 years (50%) and 68.75% patients were male. Most of the patients were primarily educated (31.25%) and middle class people was maximum (62.5%). Most patients came to hospital referred by outside doctor (62.5%) and most of them were from rural area of Bangladesh(62.5%). Main presenting symptoms were progressive deafness and duration of hearing loss for 2-5 years was 31.25%. Most of the tympanic membranes (86.75%) were normal. Rinne was negative in all cases and Weber lateralized to affected ear or more deaf ear in 93.75% cases. Patients mainly presented with 50-60 dB hearing loss. There was slightly reduced compliance in 29 cases (90%) and stapedial reflex were absent in 75% cases. Speech discrimination test was 100% in 90% of the patients. HRCT temporal bone was done in 3 cases and 2 showed thickening of foot plate of stapes. Stapedotomy was done in most of the patients (78.1%). Common problems encountered during operation was perilymph flooding (6.28%) and obliterated otosclerosis (6.28%). Most common complication was injury to Chorda tympani nerve (9.37%). Improvement of hearing was in 28 patients (87.50%) and after surgery Air-Bone gap closure more than 10 dB was in 87% of patients. Most common prosthesis used was Teflon prosthesis. Conclusion: In general the stapedotomy/stapedectomy is very successful with over 90% of people experiencing a good improvement in hearing. Sometimes the hearing remains unchanged and there is a small (approx 1-2%) chance of hearing loss. Rarely there is chance of dead ear also. Hearing results vary from surgeon to surgeon. As with all operations the best results tend to be achieved by those who do the procedure most frequently. Key Words: Otosclerosis, Stapedectomy, Stapedotomy DOI: 10.3329/bjo.v15i1.4305 Bangladesh J of Otorhinolaryngology 2009; 15(1): 10-16